Comparing diagnostic sensitivity of different needle sizes for lymph nodes suspected of lung cancer in endobronchial ultrasound transbronchial needle aspiration: Systematic review and meta‐analysis. (31st August 2021) - Yu Lee‐Mateus, Alejandra; Garcia‐Saucedo, Juan C.; Abia‐Trujillo, David; Labarca, Gonzalo; Patel, Neal M.; Pascual, Jorge M.; Fernandez‐Bussy, Sebastian
Abstract: Background: Endobronchial ultrasound transbronchial needle aspiration (EBUS‐TBNA) is a safe and minimally invasive procedure for evaluating hilar and mediastinal lymph nodes. The reported sensitivity and specificity of EBUS‐TBNA are 95% and 97%, respectively. A comparison of diagnostic sensitivity for lymph nodes suspected of lung cancer according to needle size in EBUS‐TBNA is needed. Objectives: To compare the diagnostic sensitivity of the 19‐G, 21‐G, 22‐G and 25‐G needles for lymph nodes suspected of non‐small cell lung cancer (NSCLC) using EBUS‐TBNA. Methods: A literature search from PubMed, EMBASE, LILACS, DOAJ and CENTRAL through October 2020 was performed by two reviewers. The extracted data were evaluated using STATA® and Open Meta Analyst software for meta‐analysis with a binary method model to compare sensitivity, specificity and summary receiver operating characteristic curve for each needle size. Results: Fourteen studies including 1296 participants were considered for the analysis. The overall sensitivity of EBUS‐TBNA was 88.2% (95% CI 84%, 91%) and 93% (95% CI 88%, 95%) for the 19‐G needle, 87.6% (95% CI 79.6%, 92.8%) for the 21‐G needle and 85% (95% CI 80%, 88%) for the 22‐G needle. The overall sensitivity of EBUS‐TBNA for diagnosing NSCLC was 88.3% (95% CI, 81%, 93%) and 92.9% (95% CI, 85%, 97%) for the 19‐G needle, 89.4% (95% CI 79.4%, 94.8%) for the 21‐G needle and 82.1% (95% CI 66%, 91%) for the 22‐G needle. Conclusion: The 19‐G, 21‐G and 22‐G needles present a similarly high diagnostic sensitivity in EBUS‐TBNA. The 19‐G needle provided better sample adequacy for molecular and immunohistochemical testing, improving diagnostic yield in this subgroup.